Estrogen receptor activation in response to Azadirachtin A stimulates osteoblast differentiation and bone formation in mice. Issue 12 (21st June 2019) - Kushwaha, Priyanka; Ahmad, Naseer; Dhar, Yogeshwar V.; Verma, Ashwni; Haldar, Saikat; Mulani, Fayaj A.; Trivedi, Prabodh K.; Mishra, Prabhat R.; Thulasiram, Hirekodathakallu V.; Trivedi, Ritu
Abstract: The positive effects of the sex hormone in sustaining bone homeostasis are exercised by maintaining the equilibrium between cell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is an attractive drug target, if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to be a selective tissue modifier. Using computational and medicinal chemistry, we show that Aza A binds potentially and selectively to estrogen receptor‐α (ERα) as compared with ERβ. This preferential binding of Aza A to ERα with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis, Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presents with no hyperplastic effect in the uterus. Abstract : The positive effects of the sex hormone in sustaining bone homeostasis is exercised by maintaining the equilibrium between cell activity and apoptosis. In this regard, the importance of estrogen receptors in maintaining the bone is that it is an attractive drug target, if devoid of known side effects. In this study, we show that a natural pure compound Azadirachtin A (Aza A) isolated from Azadirachta indica binds selectively to a site in the estrogen receptor, identifying itself to be a selective tissue modifier. Using computational and medicinal chemistry we show that Aza A binds potentially and selectively to estrogen receptor‐α (ERα) as compared with ERβ. This preferential binding of Aza A to ERα with good pharmacokinetic distribution in the body forms metabolites, showing that it is well absorbed. In in vivo estrogen deficiency models for osteoporosis Aza A at a much lower dose enhances new bone formation at both sites of the trabecular and cortical bone with increased bone strength and presents with no hyperplastic effect in the uterus.